Ulam Stability for First-Order Nonlinear Dynamic Equations - Bohner, Martin; Tikare, Sanket (Sarajevo Journal of Mathematics, 2024)
The purpose of this paper is to investigate Ulam stability of ﬁrstorder nonlinear dynamic equations on time scales. Based on the method of the Picard operator and using dynamic inequalities, we obtain four types of stability. In addition, as applications of our main result, we obtain new Ulam stability results for other nonlinear dynamic equations. An example is also provided to illustrate our main result.